Single-mode electrically pumped terahertz laser in an ultracompact cavity via merging bound states in the continuum - Cui, Jieyuan (2023)
Photonic bound states in the continuum (BICs) are highly localized optical modes that have found important applications in lasers, sensors, modulators, and harmonic signal generators. While possessing a higher quality factor (Q) as compared to leaky photonic modes, regular BICs (e.g., either symmetry-protected or accidental BICs) normally require large cavity sizes and are usually sensitive to the fabrication imperfections that introduce lattice disorders. Moreover, the previous demonstrations of BIC lasers are mostly based on optical pumping and operated in the visible and near-infrared regimes. Here, an electrically pumped BIC laser is demonstrated by merging two types of BIC modes based on a quantum cascade chip in the terahertz (THz) regime, which has an ultra-compact size (with a pump area around 4λ2). The measured side-mode suppression ratio (SMSR) can reach up to ≈20 dB, indicating a good single-mode performance over the entire dynamic range. In addition, the emitted beam shows a nontrivial cylindrical vector beam profile, a typical topological feature of BIC lasers. This work would pave the way for practical use of the emerging BIC concepts in pursuing ultra-compact and high-performance electrically driven laser sources, which are highly desired in advanced optoelectronics and integrated photonics.